Revisiting consumer credit laws in Malaysia / Balqis Hamdan …[et al.] - Hamdan, Balqis; Addrus, Farah Diana; Mohtar, Athirah Najiah; Shariff Roslan, Nur Liyana (2014)
Consumer credit activities namely money lending, pawn brooking and hire-purchase transactions are widely practiced in Malaysia and governed by Money lenders Act 1951, Pawnbrokers Act 1972 and Hire-Purchase Act 1967 respectively. These transactions are done by giving loans to consumers secured by their property as collateral. The purpose of this paper is to analyze the existing laws governing consumer credit transactions in Malaysia and to determine the weaknesses in the existing laws. In the same tenor, this paper will address the current flaws and insufficiency of laws governing consumer credit activities and transactions in Malaysia and reasonable suggestions are recommended in order to cope with the weaknesses.